Patterns in diet reveal foraging site fidelity of short-tailed shearwaters in the southeastern Bering Sea - Baduini, CL; Hunt, GL; Pinchuk, AI; Coyle, KO (Marine Ecology Progress Series, 2006)
The short-tailed shearwater Puffinus tenuirostris is an apex predator in the southeastern Bering Sea ecosystem. During 1997 to 1999, a period of great variability in the Bering Sea, we used a multi-pronged approach to study transfer of carbon and nitrogen to short-tailed shearwaters through analysis of stomach contents of birds collected while foraging, and stable isotope and fatty acid composition of tissues from shearwaters and their prey. Two conclusions result from these 3 analyses of feeding history. First, short-tailed shearwaters demonstrated localized differences in diet with respect to sampling location and season, indicating that shearwaters feed in discrete locations long enough (several weeks) to reflect regional differences in prey availability. Second, elevated δ15N levels (∼1 to 2‰) in the liver of shearwaters in the fall of 1997 and 1998 were likely a response to nutritional stress and overturn of nutrients in the tissues of birds or elevated isotope levels in tissues of prey, rather than an increase in the trophic level of the diet. Over the 3 yr period, shearwater diets switched from adult euphausiids Thysanoessa raschii and T. inermis (usually females with spermatophores) taken in spring to an increase in the amount of fish (Pacific sandlance Ammodytes hexapterus), juvenile Gadidae fishes and larval walleye pollock Theragra chalcograma particularly in fall (1997 excepted). For each location and year, there was a consistent trend in isotopic values, with an increase of 3 to 5‰ for δ15N and 1 to 3‰ for δ13C between shearwaters and their primary prey. The resolution of our sampling techniques indicates little movement of shearwater flocks among sample locations for periods of up to several weeks. © Inter-Research 2006.